A produção da escrita do texto argumentativo de alunos do 9° ano do ensino fundamental - Silva, Fernanda Cavalcante Barbosa e (2018)
Reading and writing are essential skills for school life, with respect to the construction of knowledge for the development of student autonomy, with a view to the formation of subjects capable of interacting in the most diverse communicative situations. The present work has as starting point the observation of problems in the written production of argumentative texts of the students of the 9th grade of Elementary School of a public school, located in Fortaleza - CE. Thus, the questions that guided this investigation were whether the argumentative texts produced by the students presented a point of view on a particular question; if these texts revealed the use of consistent arguments for the support of the point of view and, finally, if the students correctly used discursive-argumentative articulators in the text produced. In order to answer these questions, we define as general objective of this work, to investigate the writing of argumentative texts produced by these students, adopting, mainly, the perspective of textual linguistics. Theoretically, this research adopted the postulates of the investigations of Koch and Elias (2017), Marcuschi (1983, 2002, 2008, 2010) on the text, besides other authors whose works discuss the argumentation and the teaching of the argumentative text, such as Platin (2008, 2011), Faraco (1992) and Possenti (2017). Methodologically we opted for an action research, following a qualitative approach seeking the orientations of the works of Brandão (1990), Bogdan and Biklen (1994) and Thiollent (1998). In order to be a proposal for intervention work, the data were collected through the application of a didactic sequence, the corpus of the research being composed of the initial and final textual productions of the students. The analysis of the data collected in these two moments was made from the categories based on Koch and Elias (2017) and Possenti (2017), which are: the point of view and its relation with the arguments; the argumentative strategies and the discursiveargumentative articulators. The problems observed in the initial productions, related to the general organization of the texts, the use of cohesive elements, difficulties in the construction of arguments when producing texts that require a positioning by the student, directed the pedagogical activities throughout the intervention. When comparing the textual productions of the students before and after the development of the proposal, we noticed the effectiveness of the work done through the didactic sequence, focusing on the argumentation. Significant improvement was observed in the development of communicative competence. The students produced texts in which more consistent arguments were observed, identifying positions more critically from important social issues. As a conclusion, the research made it possible to deepen the identification of students' difficulties in the construction of argumentative texts as well as to observe and record their overcoming.